Pendidikan Agama Islam di Era Globalisasi Serta Pengaplikasiannya Dalam Lingkungan Sekolah Dasar - Kinanti Anisa Lestari; Kiki Fitriani; Farah Firdausa Muchtari; Maitsa Sajidah (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
Globalization has a major impact on all aspects, including the world of education, including Islamic religious education. The purpose of this research is to determine the positive and negative impacts of Islamic religious education in the era of globalization, to determine the effect of globalization in the elementary school environment, to find solutions in dealing with globalization in the elementary school environment, and the application of Islamic religious education in the era of globalization in elementary schools. The method used in the research is a literature study (library research). The types of data used in this research are primary data and secondary data. Sources of data used in the research in the form of written sources taken from various previous scientific journals. The data analysis technique used in this research is in the form of qualitative descriptive data analysis. Based on the detailed discussion regarding Islamic religious education in the Globalization Era and its application in Elementary Schools, it can be understood that Islamic religious education in this globalization era needs to be handled further, so that the morals and character of the students can be directed properly.